"THE EFFECT OF BRAND EQUITY ON iPHONE PURCHASING DECISIONâ€ (Study at Faculty of Economics and Business Students, University of Brawijaya) - Oktareza, Rendy (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this study was to determine the effect simultaneously of the variables Brand Awareness, Perceived Quality, Brand Association and Brand loyalty on iPhone purchasing decisions, and to determine the effect Independently of the variables Brand Awareness, Perceived Quality, Brand Association and Brand loyalty on iPhone purchasing decision The population in this study is students at Faculty of Economics and Business, University ofÂ  Brawijaya, class of 2009 till 2011, which is still active. Sampling technique in this study is accidental sampling and the minimum number of samples taken in this study was 80 respondents. Data analysis techniques used multiple linear regression test, F test, t test and coefficient of determination. The research proves that Brand Awareness variables (X1), Perceived Quality (X2), Brand Association (X3), Brand loyalty (X4) simultaneously have a significant influence onÂ  students decision to buy iPhone (Y). The results also prove that the variable Brand Awareness (X1), Perceived Quality (X2), Brand Association (X3), Brand loyalty (X4) partially significant effect on students decision to buy iPhone (Y). The results show Brand Awareness variables most affect the students decision to buy an iPhone in comparison to other variables. The test results of coefficient of determination (R2) equal to 57% of students in the purchasing decision is influenced by variables iPhone Brand Awareness, impression quality, brand association, brand loyalty and the balance of 43% is influenced by other factors not examined. Keywords: Brand Equity, Purchasing Decision.